Efektivitas Penggunaan Ensiklopedia Berbasis Teknologi Sebagai Sumber Belajar di Sekolah Menengah Atas (SMA): Literature Review - Tri Mulyani; Armiati Armiati (Jurnal Ecogen, 2021)
Abstract : Objective: To determine the effectiveness of technology-based encyclopedias as learning resources to increase motivation and learning outcomes in the learning process. The method used in this article uses the literature review method, a source obtained on the Google Scholar website with problems in the past 5 years. From 8 articles, found the development of tenology-based encyclopedias as a very effective learning resource used in the learning process by using the ADDIE, 4-D development model, and Borg and Ball development models. Then in the use of technology-based learning resource encyclopedias this is very feasible to use in the learning process both in the class room and independently at home. So, the development of technology-based learning resource encyclopedia that is able to be a source of learning in addition to textbooks that are used by students to add insight, enrich information and understanding and can increase motivation and learning outcomes. Conclusion: This literature review found the use of technology-based encyclopedias as learning resources. Technology-based encyclopedias are one of the sources of appropriate and effective learning to increase motivation, learning outcomes, interest in reading to add insight, knowledge and understanding of students. Keywords : effectiveness, encyclopedia, learning resources